ABSTRACTANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI BUYING DECISIONPADA PRODUK FASHION WANITA DI SHOPEE(Studi Kasus Mahasiswa Universitas An Nuur Kabupaten Grobogan) - Intan Diah Prihastuti; Winarsih Winarsih (LPPM Universitas An Nuur, 2025)
Background & Purpose: Rapid development of the fashion industry in the digital era has driven significant growth in online shopping, particularly through the Shopee platform. Purchasing decisions are influenced by consumer reviews, product attractiveness, and turbo marketing. In practice, consumer reviews often become a key consideration, although previous studies have reported inconsistent findings. To address this issue, the present study aims to examine the effect of consumer reviews, product attractiveness, and turbo marketing on buying decisions for women’s fashion products on Shopee, using a case study of students at An Nuur University, Grobogan Regency. Method: This research employed a quantitative approach with a survey method. The population consisted of female students at An Nuur University who had purchased women’s fashion products on Shopee. A purposive sampling technique was applied with criteria of female consumers who had purchased fashion products on Shopee, resulting in a total of 126 respondents. Data were collected through a structured questionnaire using a Likert scale. The independent variables in this study were Consumer Review (X1), Product Attractiveness (X2), and Turbo Marketing (X3), while the dependent variable was Buying Decision (Y). The collected data were analyzed using SPSS version 24 through validity and reliability testing, classical assumption testing, multiple linear regression, t-tests, and the coefficient of determination (R²). Results: findings reveal that consumer reviews have a positive and significant effect on buying decisions. Product attractiveness, however, shows a negative and significant effect on buying decisions. Furthermore, turbo marketing contributes positively and significantly to buying decisions. Therefore, these three factors are essential elements that shape consumers’ purchase decisions in the online fashion industry. Conclusion : study concludes that purchase decisions on Shopee are more strongly influenced by consumer reviews and service responsiveness than by product attractiveness alone. This highlights the importance of trust, real experiences, and seller responsiveness in shaping consumer buying behavior in the online fashion market. Suggestion : For fashion sellers on e-commerce platforms, it is recommended to encourage genuine and positive consumer reviews, maintain product quality and keep up with fashion trends even though product attractiveness does not always guarantee purchase decisions, and optimize turbo marketing through fast responses and timely delivery to improve customer satisfaction and loyalty. Keywords: Consumer Review, Product Attractiveness, Turbo Marketing, Buying Decision